Supply Chain Resilience: Strategies for Mitigating Disruptions and Enhancing Business Continuity - Suprayitno, Degdo (Management Studies and Business Journal (PRODUCTIVITY), 2024)
In the context of globalization and market volatility, supply chain resilience has become critical for the continuity of business operations. This research analyzes differences in supply chain risk management practices between small and large companies in facing disruptions. Using the systematic literature review method, researchers collected and analyzed related articles from various international databases. The analysis results show that small companies tend to adopt simpler and reactive risk management strategies, while large companies have a more structured and proactive approach. The implication of this research is the need for a risk management approach that is tailored to the size and characteristics of the company to increase supply chain resilience.